2017
DOI: 10.1080/23320885.2017.1396902
|View full text |Cite
|
Sign up to set email alerts
|

Early mobilizing and dangling of the lower leg after one-stage reconstruction of Achilles tendon and overlying tissue defect using an anterolateral thigh flap with vascularized fascia lata

Abstract: We have treated two patients who had an Achilles tendon and overlying tissue defect using an anterolateral thigh flap with fascia lata. Postoperatively, skeletal suspension of the affected leg and intra-arterial heparin infusion were performed for seven days. Six weeks postoperatively, the patients could walk again.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
2
0
2

Year Published

2019
2019
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 25 publications
0
2
0
2
Order By: Relevance
“…The review concluded that more research is needed to determine optimal flap training but that initiating the protocol sooner had physiological benefits for the patient. Okochi et al17 highlighted a case study where the individual was also able to dangle on postoperative day 7. This protocol differed from Mcghee et al's previously discussed one.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The review concluded that more research is needed to determine optimal flap training but that initiating the protocol sooner had physiological benefits for the patient. Okochi et al17 highlighted a case study where the individual was also able to dangle on postoperative day 7. This protocol differed from Mcghee et al's previously discussed one.…”
Section: Discussionmentioning
confidence: 99%
“…The review concluded that more research is needed to determine optimal flap training but that initiating the protocol sooner had physiological benefits for the patient. Okochi et al 17 Copyright © 2021 Academy of Acute Care Physical Therapy, APTA. Unauthorized reproduction of this article is prohibited.…”
Section: Review Articlementioning
confidence: 99%
“…2 ) 51 . Dies wird von vielen Autoren als Technik der Wahl für die kombinierte vaskularisierte tendokutane Rekonstruktion angesehen, da neben den genannten Vorteilen der vaskularisier- ten Faszientransplantate eine ausgesprochene Größenvariabilität und gute Konturanpassung der ALT-Lappenplastik bestehen 51 52 53 54 55 56 57 58 59 60 61 62 . Ein erhöhter Body-Mass-Index und eine periphere arterielle…”
Section: Ergebnisseunclassified
“…2) [51]. Dies wird von vielen Autoren als Technik der Wahl für die kombinierte vaskularisierte tendokutane Rekonstruktion angesehen, da neben den genannten Vorteilen der vaskularisierten Faszientransplantate eine ausgesprochene Größenvariabilität und gute Konturanpassung der ALT-Lappenplastik bestehen [51][52][53][54][55][56][57][58][59][60][61][62]. Ein erhöhter Body-Mass-Index und eine periphere arterielle Verschlusskrankheit wurden als Prädiktoren für ein schlechtes klinisches Endergebnis nach ALT-Lappenplastik mit vaskularisierter Fascia lata identifiziert, währenddessen das Patientenalter keinen Einfluss auf das funktionelle Ergebnis hatte [54].…”
Section: Tendokutane Defekte -Resektion Der Sehnenstümpfe Mit Singulä...unclassified